Acute Hepatitis in a Yemeni Immigrant Associated with Khat: A “Biological Amphetamine” Carried in Cultures - Harish Patel; Kishore Kumar; Rajesh Kumar Essrani; Masooma Niazi; Jasbir Makker; Suresh Kumar Nayudu (Clinics and Practice, 2021)
Viral infections, alcohol, hepatic steatosis, autoimmunity medications and herbal supplements are common etiologies of hepatitis. Khat (Catha Edulis) is a commonly used recreational substance in East African and Middle Eastern countries. Khat has been reported in the literature to be associated with hepatotoxicity, which can present in several forms, including chronic liver disease. The possible pathogenesis of liver injury could be secondary to biochemical components of Khat itself or additives such as pesticides or preservatives. An autoimmune mechanism of liver injury has also been postulated, supported by sparse evidence. We present a case of a Yemeni immigrant with acute hepatitis whose fear about social norms and breaching confidentiality made it challenging to identify Khat as being the underlying cause. A 34-year-old man from Yemen presented with right upper quadrant pain of one day duration. He had predominantly elevated transaminases with mild elevation in bilirubin. His investigations were negative for the viral, metabolic or biliary etiology. A persistent focus on clinical history and the well-established physician–patient relationship revealed a history of Khat use. The liver biopsy finding of lobular hepatitis was compatible with drug-induced liver injury and established the finding of Khat hepatotoxicity. Subsequently, the patient improved with conservative management.